Change trend analysis of the time-series shadow-eliminated vegetation index (SEVI) for the Wuyishan Nature Reserve with the Sen+Mann-Kendall method. Issue 1 (February 2021) - Jiang, Hong; Wu, Yongfeng
Abstract: In order to reveal the characteristics of spatial distribution and dynamic change of the forest in the Wuyishan Nature Reserve from 2000 to 2019, the recently proposed shadow-eliminated vegetation index (SEVI) and the method of Sen+Mann-Kendall were used together in this study. The results show a trend of "decreasing first and then increasing" of vegetation cover change of the Reserve during the sub-periods of 2000-2011 and 2012-2019, but, as a whole, the vegetation cover of the Reserve was improved during 2000-2019, with 43.76% slight improvement and 55.18% significant improvement, approximately.